2011 12th International Carpathian Control Conference (ICCC) 2011
DOI: 10.1109/carpathiancc.2011.5945880
|View full text |Cite
|
Sign up to set email alerts
|

Optimal location of an active segment of magnetorheological fluid layer in a sandwich plate

Abstract: In the present study a sandwich plate, of rectangular form, with magnetorheological (MR) fluid core is investigated. The plate consists of two outer layers made of aluminium and an MR fluid layer in between. The plate edges are clamped. It was assumed that the aluminium layers are pure elastic. The energy is dissipated in MR fluid layer. Additional assumptions concerning displacements, deformations and stresses are introduced in calculations. The active segment of MR fluid layer is placed in various parts of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…For instance, the MR fluid treatments closed to the supports of simply supported and clamped sandwich beams yielded higher modal damping factors corresponding to all the modes. Snamina (2011) employed the classical plate theory and energy method to find optimal number and locations of the MR segments in the core layer of a sandwich plate to maximize the energy dissipation of the structure. The objective function was considered as…”
Section: Optimum Design Of Partially Treated Sandwich Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the MR fluid treatments closed to the supports of simply supported and clamped sandwich beams yielded higher modal damping factors corresponding to all the modes. Snamina (2011) employed the classical plate theory and energy method to find optimal number and locations of the MR segments in the core layer of a sandwich plate to maximize the energy dissipation of the structure. The objective function was considered as…”
Section: Optimum Design Of Partially Treated Sandwich Structuresmentioning
confidence: 99%
“…The design of a partially treated MR/ER sandwich structure requires finding an appropriate configuration of the treatments so that it yields the maximum controllability and vibration suppression capability of the structure in terms of stiffness and damping. For this purpose, different optimization problems on MR/ER sandwich structures have been formulated (Mohammadi and Sedaghati, 2012c; Rajamohan et al, 2010b; Snamina, 2011). Rajamohan et al (2010b) proposed three optimization problems to investigate the effect of MR layout on dynamic responses of partially treated MR beam.…”
Section: Dynamic Characteristics and Optimum Design Of Partially Treated Mr/er Sandwich Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to describe the motion of a three-layered sandwich plate which consists of ER core and nanocomposite facesheets, the following assumptions can be expressed as [21,22]: (i) there is no slip at the interface of ER core and nanocomposite facesheets; (ii) all points placed on normal to the plate in its equilibrium state move with the same transverse displacement; (iii) the Young's modulus of the ER fluid is negligibly small compared with the nanocomposite facesheets and thus, the normal stresses in the ER fluid core are neglected. Based on the classical plate theory (CPT), the displacement fields of nanocomposite facesheets can be given by [23]:…”
Section: Sandwich Plate Rested On Orthotropic Visco-pasternak Foundationmentioning
confidence: 99%
“…They illustrated that by enhancing the magnetic field severity, the modal loss factor, unlike the natural frequency, decreases. In other researches, desirable position of an active part in a sandwich plate with MR layer was conducted by Snamina (2011). Gedik et al (2012) indicated stable dynamic demeanor of a MR fluid layer between two fixed plates subjected to an identical magnetic field.…”
Section: Introductionmentioning
confidence: 99%